The Role of Anti-EGFR Monoclonal Antibody in mCRC Maintenance Therapy - Yuan, Meiqin; Wang, Zeng; Lv, Wangxia; Pan, Hongming (Frontiers in Molecular Biosciences, 2022)
Background: Epidermal growth factor receptor (EGFR) monoclonal antibodies (mAb) combined with chemotherapy in patients with RAS wild-type metastatic colorectal cancer (mCRC) can alleviate and stabilize the disease, effectively prolong the progression free survival (PFS) and overall survival (OS), and improve the objective remission rate (ORR), which is the first-line treatment standard scheme for Ras wild-type mCRC currently. But whether anti-EGFR mAb can be used for maintenance treatment after first-line treatment of mCRC remains controversial. We review the recent studies on anti-EGFR mAb. The contents include three parts, anti-EGFR mAb in mCRC and its status in first-line therapy, establishment of the maintenance treatment pattern after the standard first-line treatment for mCRC, and research progress of anti-EGFR mAb in mCRC maintenance therapy. More studies support the maintenance treatment of anti-EGFR mAb, but some researchers raise the problems about high cost and drug resistance. Although lack of the maintenance evidence of anti-EGFR mAb, especially lack of large-scale phase III prospective clinical trials, with the emergence of new evidence and more accurate screening of treatment dominant groups, maintenance therapy with anti-EGFR monotherapy or anti-EGFR combined with fluorouracil-based schemes after first-line chemotherapy combined with anti-EGFR therapy, might strive for more treatment opportunities, optimize treatment strategies and prolong treatment continuity, and finally leading to more survival benefit for suitable patients.